Luminescent κ-Carrageenan-Based Electrolytes Containing Neodymium Triflate - Nunes, S. C. (2019)
In recent years, the synthesis of polymer electrolyte systems derived from biopolymers for the development of sustainable green electrochemical devices has attracted great attention. Here electrolytes based on the red seaweeds-derived polysaccharide κ-carrageenan (κ-Cg) doped with neodymium triflate (NdTrif3) and glycerol (Gly) were obtained by means of a simple, clean, fast, and low-cost procedure. The aim was to produce near-infrared (NIR)-emitting materials with improved thermal and mechanical properties, and enhanced ionic conductivity. Cg has a particular interest, due to the fact that it is a renewable, cost-effective natural polymer and has the ability of gelling in the presence of certain alkali- and alkaline-earth metal cations, being good candidates as host matrices for accommodating guest cations. The as-synthesised κ-Cg-based membranes are semi-crystalline, reveal essentially a homogeneous texture, and exhibit ionic conductivity values 1–2 orders of magnitude higher than those of the κ-Cg matrix. A maximum ionic conductivity was achieved for 50 wt.% Gly/κ-Cg and 20 wt.% NdTrif3/κ-Cg (1.03 × 10−4, 3.03 × 10−4, and 1.69 × 10−4 S cm−1 at 30, 60, and 97 °C, respectively). The NdTrif-based κ-Cg membranes are multi-wavelength emitters from the ultraviolet (UV)/visible to the NIR regions, due to the κ-Cg intrinsic emission and to Nd3+, 4F3/2→4I11/2-9/2.